Combination Cancer Therapy with Immune Checkpoint Blockade: Mechanisms and Strategies - Patel, Shetal A. (Immunity, 2018)
The success of immune checkpoint blockade in patients with a wide variety of malignancies has changed the treatment paradigm in oncology. However, combination therapies with immune checkpoint blockade will be needed to overcome resistance and broaden the clinical utility of immunotherapy. Here we discuss a framework for rationally designing combination therapy strategies based on enhancing major discriminatory functions of the immune system that are corrupted by cancer – namely, antigenicity, adjuvanticity, and homeostatic feedback inhibition. We review recent advances on how conventional genotoxic cancer therapies, molecularly targeted therapies, epigenetic agents, and immune checkpoint inhibitors can restore these discriminatory functions. Potential barriers that can impede response despite combination therapy are also discussed.